Touch perception reveals the dominance of spatial over digital representation of numbers - Brozzoli, Claudio; Ishihara, Masami; Göbel, Silke M; Salemme, Roméo; Rossetti, Yves; Farnè, Alessandro (Proceedings of the National Academy of Sciences - PNAS, 2008)
We learn counting on our fingers, and the digital representation of numbers we develop is still present in adulthood [Andres M, et al. (2007) J Cognit Neurosci 19:563-576]. Such an anatomy-magnitude association establishes tight functional correspondences between fingers and numbers [Di Luca S, et al. (2006) Q J Exp Psychol 59:1648-1663]. However, it has long been known that small-to-large magnitude information is arranged left-to-right along a mental number line [Dehaene S, et al. (1993) J Exp Psychol Genet 122:371-396]. Here, we investigated touch perception to disambiguate whether number representation is embodied on the hand ("1" = thumb; "5" = little finger) or disembodied in the extrapersonal space ("1" = left; "5" = right). We directly contrasted these number representations in two experiments using a single centrally located effector (the foot) and a simple postural manipulation of the hand (palm-up vs. palm-down). We show that visual presentation of a number ("1" or "5") shifts attention cross-modally, modulating the detection of tactile stimuli delivered on the little finger or thumb. With the hand resting palm-down, subjects perform better when reporting tactile stimuli delivered to the little finger after presentation of number "5" than number "1." Crucially, this pattern reverses (better performance after number "1" than "5") when the hand is in a palm-up posture, in which the position of the fingers in external space, but not their relative anatomical position, is reversed. The human brain can thus use either space- or body-based representation of numbers, but in case of competition, the former dominates the latter, showing the stronger role played by the mental number line organization.